An Interdisciplinary Approach to Islamic Religious Education in Elementary Schools - Ainur Rofi'ah, Lyza Habibah; Yuniarti, Elma; Nikmah, Zumrotul Fitriana; Royatuz Zaman, Vela Shofa (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
This research aims to address the limited implementation of an interdisciplinary approach in Islamic religious education for elementary school students. An interdisciplinary approach involves integrating two educational disciplines to explain religious content alongside non-religious material, offering a potential solution to reduce the educational dichotomy in Indonesia. While incorporating interdisciplinary methods in education, particularly at the elementary level, is not a new concept, it remains underutilized due to the limited student response, which often discourages educators from applying it. This qualitative descriptive study involved fifth-grade students from SDI Insan Kamil Tuban. Findings from the implementation of the interdisciplinary approach in these classes indicated that not all students were enthusiastic, though high-performing students showed greater engagement. These students, with their critical thinking skills, responded positively, creating a more dynamic and enjoyable classroom environment compared to the previous monotonous setup. The experiment to enhance learning motivation was deemed 75% successful, as only a portion of students displayed enthusiasm. Thus, educators are encouraged to be more innovative and creative in designing engaging lessons, which could be facilitated by surveying students' learning preferences to reduce passivity. An active classroom, in turn, can lead to improved learning outcomes.